2015
DOI: 10.1159/000440858
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Frontotemporal Lobar Degeneration in Northern Finland

Abstract: Background: Frontotemporal lobar degeneration (FTLD) is responsible for as many as every fifth case of early-onset dementia. Very few epidemiological studies of FTLD have been conducted; there are no published epidemiological data of FTLD from Finland or the other Nordic countries. The C9ORF72 expansion-associated FTLD is common in Finland; thus, the prevalence of FTLD is expected to be high in this population. Methods: We retrospectively evaluated the incidence and prevalence of FTLD in university hospital se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Their reported prevalence (0.02-0.31 per 1000) and incidence (0.013 and 0.167 per 1000) rates also ranged widely. After completion of our systematic review, three otherwise eligible studies 44 - 46 that reported on the incidence and/or prevalence of FTD were published. Their estimates fall within the range we report and do not change our main findings.…”
Section: Discussionmentioning
confidence: 99%
“…Their reported prevalence (0.02-0.31 per 1000) and incidence (0.013 and 0.167 per 1000) rates also ranged widely. After completion of our systematic review, three otherwise eligible studies 44 - 46 that reported on the incidence and/or prevalence of FTD were published. Their estimates fall within the range we report and do not change our main findings.…”
Section: Discussionmentioning
confidence: 99%
“…ALS is the most frequently occurring form of motor neuron disease, affecting approximately 2–4/100,000 individuals (Johnston et al , 2006), and is characterized by progressive paralysis typically leading to death within two to three years after onset. FTD is the second most common form of presenile dementia and affects approximately 20/100,000 individuals between the ages of 45 and 65 (Onyike and Diehl-Schmid, 2013; Luukkainen et al , 2015). FTD presents heterogeneously and is divided into three clinical syndromes; behavioral variant, semantic dementia, and progressive nonfluent aphasia (Neary et al , 1998).…”
Section: Ran Translation At Ggggcc and Ggcccc Repeats In C9 Als/ftdmentioning
confidence: 99%
“…1 Frontotemporal dementia is the second cause of presenile dementia, and bvFTD represents the most frequent subtype. 2,3 This form is clinically characterized by prominent behavioral disturbances, including disinhibition, impulsivity, perseverations, and loss of empathy, that are associated with deterioration in social conduct and impairment of cognition. 1,4 Recently, a complex and intriguing relationship between bvFTD and several psychiatric disorders has been described.…”
Section: Introductionmentioning
confidence: 99%